The microbiology of necrotizing pancreatitis and its impact on in-hospital and 1-year all-cause mortality. Issue 6 (June 2020) - Biberci Keskin, Elmas; Okay, Gülay; Muhiddin, Duygu; Sharif, Rasul; Taşlidere, Bahadir; Şentürk, Hakan
Abstract : Background/objectives: The data regarding the microbial spectrum in necrotizing pancreatitis and its impact on mortality is limited. Therefore, in this study, we aimed to investigate the agents identified in cultures and their impact on in-hospital and 1-year all-cause mortality. Methods: Patients with necrotizing pancreatitis were retrospectively included in the study. Based on culture results, patients were classified as either negative culture or positive culture necrotizing acute pancreatitis. The main outcomes of the study were the identification of agents isolated in patients with pancreatic necrosis and to assess in-hospital, 30-day and 1-year all-cause mortality according to culture results. Results: In total, 109 patients of whom 33 had positive cultures were included in the study. Most positive cultures were polymicrobial (66%) with a marked gram-negative bacterial dominance (63%). Klebsiella spp. were the most common identified pathogens. The patients a with positive culture had worse outcomes in terms of in-hospital, 30-day and 1-year all-cause mortality compared to patients with sterile culture results (n = 9, 27.3% vs. n = 4, 5.3%, P < 0.01 for in-hospital mortality; n = 11, 33.3% vs. n = 5, 6.6%, P < 0.01 for 30-day mortality; and n = 14, 42.4% vs. n = 10, 13.2%, P < 0.01 for 1-year mortality). Conclusion: When a microorganism was identified in patients with necrotizing acute pancreatitis, it was mostly polymicrobial in etiology with a gram-negative bacterial dominance. In our cohort, Klebsiella spp. were the most common isolated organisms. Especially the patients with polymicrobial etiology showed a very poor outcome both in-hospital and in the long-term. Local hospital flora may have an impact on culture results.